KOMUNIKASI KELOMPOK DALAM MENINGKATKAN KUALITAS KERJA TEAM REDAKSI BIDANG BERITA LEMBAGA PENYIARAN PUBLIK TVRI SUMATERA UTARA DI MEDAN - SANNY APRILINDA DAMANIK; Syukur Kholil Dalimunthe (JURNAL PROINTEGRITA, 2018)
This study aims to determine the group communication in improving the quality of work of Team Editorial News Field Broadcasting Institution TVRI North Sumatra in Medan. Three questions that is how the planning of organizational communication: 1) How the implementation of group communication in news team news team at Broadcasting Institution TVRI Sumatera Utara in Medan; 2) How the quality of news team editorial team at Broadcasting Institution TVRI Stunatera Utara in Medan; and 3) How the implementation of communication group to improve the quality of news team editorial team at Public Broadcasting Institution TVRI Sumatera Utara in Medan. The theoretical framework used is group communication and interpersonal communication and quality study. The model of group communication according to Michael Burgoon in Abu Huraerah and Joseph A. Devito. This research uses qualitative approach through case study model design. Data collection techniques were conducted through: (1) interview, (2) observation, (3) documentation study, and (4) reference searching. Informants were taken by purposive sampling technique. The data is processed using Sugiyono model, that is through three steps, the first data reduction (data reduction), second presentation data (data display), the third withdrawal conclusion or verification conclusion. The result of the research is known that the Group Communication in Improving the Quality of Work of the Editorial Team of News Field of Public Broadcasting Institution of TVRI Sumatera Utara in Medan. In improving the quality of editors team news field limited Human Resources (HR) coupled with the age of employees 50 years and over. Rugged device equipment and software does not support because it still uses the old components. The new ones do not fit the needs. In assigning or broadcasting a story there are several crews involved and elements of the editorial team only use the What's App (WA) Group to coordinate the news event to be aired. Taking into account the purpose of improving the quality of the editorial team work in the field of news, it is expected LPP TVRI North Sumatra in Medan news field should increase human resources through training and education-education so that professionalism every workplace is owned and not double work. LPP TVRI North Sumatra in Medan is expected to balance the needs of contemporary technology so that infrastructure and facilities with other TVs can compete. LPP TVRI Sumatera Utara in Medan news field can turn on Unit Production and Unit Production Manager (UPM) because both of these fields are in charge of coordinating and responsible for production process. Relive editorial meetings, and technology experts.